Protecting plants and killing pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Joseph Mambu of the Cotton Development Corporation in Cameroon with advice on effective pesticide use and other pest control activities.